Physical and mechanical properties of porous asphalt incorporating bamboo fiber - Md Shahnewaz, Shoaib (2023)
Porous Asphalt (PA) is a highly permeable asphalt surface used to create and maintain permeable pavements for storm water management and runoff reduction. Under the impacts of repetitive vehicle loads, warm weather, and heavily rainfall, the structure was vulnerable to deterioration from cracking, rutting, stripping, and quick aging. This research aims to investigate the role of bamboo fiber in improving the physical, mechanical and morphological properties and overcome the issue related to porous asphalt (PA). PA specimens containing different percentages of bamboo fiber were examined to see which samples offered the greatest performance according to the requirements. In this research three physical performance test which is (binder draindown, permeability and cantabro test) and three mechanical performance test (marshall stability, resilient modulus and indirect tensile strength test) was conducted to justify the study objective. This research used two types of aggregate Grade A and B with four different percentage of bamboo fiber (0.2%, 0.3%, 0.4%, 0.5%) and also a sample without bamboo fiber (0%) as the controlled sample. In this research 120 PA samples where 96 fiber modified PA and 24 control PA samples were used. The total aggregate weight was 1100 g for each sample, and the average thickness of each sample between 66 mm to 70 mm. In this research, four different percentages of bamboo fiber were mixed with PEN 60/70 bituminous binder. Binder drain-down test is conducted in a wire mesh placed inside the tray. The result indicated that 0% and 0.5% had the highest drain-down percentages and 0.2% had the lowest drain-down percentage. A lesser percentage of bamboo fiber is suitable for PA. Sample 0.2% modified PA grade B had the highest (1.41m/s) permeability coefficient value. This outcome supports the modified bamboo fiber greater PA value. According to the theory, all bamboo modified PA samples (0.2%, 0.3%, 0.4%, and 0.5%) had a significant outcome in comparison to the other physical performance tests. The control sample was the exception. Meanwhile, the marshall stability test bamboo modified 0.4% PA sample achieved a maximum stability average value of 9.842 kN for grade A and 9.391 kN for grade B, compared to the control 0% PA sample stability value of 5.892 kN and 8.545 kN. Every three-pulse repetitive period for both temperature (250℃ and 400℃) and grade (A and B) 0.3% obtained the ideal resilient modulus average value (3156 MPa and 2266 MPa). However, indirect tensile strength gains the greatest value at 0.3% bamboo modified PA, 1.087 kPa for grade A and 0.4% bamboo modified PA, 0.961 kPa for grade B. As a result, when bamboo fiber was combined with PA, all mechanical properties tests showed a significant value increase. Based on SEM images, the control sample showed more cracks in the contrast bamboo modified PA. On every occasion, a Silicon (Si) chemical component is found in both control and bamboo modified PA EDX images. From the findings, it can be concluded that proper concentration and exact subsistence of bamboo fiber can enhance PA physical and mechanical properties. For future research, it is suggested that the influence of various bamboo fibre lengths on porous asphalt performance is investigated, as well as the development of an acceptable design technique for PA mixtures that would provide PA with quality service history.